Srategi Pemasaran RSUD Prof. Dr. H.M. Chatib Quzwain Sarolangun Jambi Tahun 2018 - Bajri, Ahmad; Sulistiadi, Wahyu (UI Scholars Hub, 2019)
Undang-Undang No.36/2009 Pasal 34 Ayat 2 states that the community has the right to obtain health protection from the state. In order to regulate comprehensive health protection for the community, the government requires all hospitals, both government and private hospitals to take part in the National Health Insurance / JKN Program. In this regard, the General Hospital of Prof. Dr. H.M. Chatib Quzwain is a class C regional hospital that has only been operating since 2008, so there are still many shortcomings and limitations, especially in the field of services and supporting facilities. Knowing this, efforts have been made to add facilities by the regional government from year to year, such as the addition of the number of specialist doctors and the addition of specialist poly services. Now, RSUD Prof.Dr.H.M. Chatib Quzwain has a BLUD status, so hospitals can use and manage funds obtained from services independently. Then, a problem that has yet to be overcome has emerged, namely a shortage of specialist doctors. This shortage caused the hospital to cause a decrease in the number of patients because patients had to be referred to hospitals that were more fully equipped with specialist doctors and supporting facilities, such as Siloam Hospital, Raden Mataher Hospital, Dr. Hospital. Bratanata, and Mayang Medical Center Hospital. With the reduction in the number of patients served in Chatib Quzwain Sarolangun General Hospital, automatically, hospital revenues also decrease, as well as operational financing capabilities. Therefore, Prof. RSUD Dr. H.M. Chatib Quzwain must arrange a marketing strategy to maintain and increase the number of patients visiting for the smooth operation of the hospital. Based on this research, it is known that innovation drives productivity in the nonprofit sector and in the commercial sector. The biggest progress came not from additional improvements in efficiency, but from new and better approaches.